What Factors Exacerbate and Mitigate the Risk of Gender-Based Violence During COVID-19? : Insights from a Phone Survey in Indonesia - Halim, Daniel; Can, England Rhys; Perova, Elizaveta (World Bank, Washington, DC, 2021)
One in three Indonesian women have experienced Gender-Based Violence (GBV) in their lifetime. The Coronavirus (COVID-19) pandemic may further exacerbate the risks of GBV. First, additional stress due to health risks and economic uncertainty is likely to trigger conflict within family. Second, more time spent in the same physical space with potential perpetrators due to lockdowns may also increase the likelihood of abuse. We collected data on exposure to GBV through a phone survey to understand the factors that pose the greatest risk and policy interventions that may effectively protect women. In-person data collection was not possible due to health concerns associated with the Coronavirus (COVID-19) pandemic. In order to not jeopardize the safety of the respondents through backlash from perpetrators living in the same households, we did not ask questions about violence directly. Rather, based on consultations with GBV experts, we developed a series of proxy questions, which allowed us to infer the likely exposure to violence.